Knowledge Graph Question Answering using Graph-Pattern Isomorphism - Vollmers, Daniel; Jalota, Rricha; Moussallem, Diego; Topiwala, Hardik; Ngonga Ngomo, Axel-Cyrille; Usbeck, Ricardo (CoRR)

MLCheck- Property-Driven Testing of Machine Learning Models - Sharma, Arnab; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille; Wehrheim, Heike (CoRR)

Open Data Portal Germany (OPAL) Projektergebnisse - Wilke, Adrian; Ngonga Ngomo, Axel-Cyrille (CoRR)

Out-of-Vocabulary Entities in Link Prediction - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (CoRR)

DRILL- Deep Reinforcement Learning for Refinement Operators in ALC - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (CoRR)

Trust Me, I’m Confident – Are Confident Members of the Crowd Better at Evaluating Business Model Ideas? - Laux, Florian; Görzen, Thomas (Proceedings of the 42nd International Conference on Information Systems (ICIS))

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

ALPACA: Application Layer Protocol Confusion - Analyzing and Mitigating Cracks in TLS Authentication - Brinkmann, Marcus; Dresen, Christian; Merget, Robert; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schwenk, Jörg; Schinzel, Sebastian (30th USENIX Security Symposium (USENIX Security 21))

Raccoon Attack: Finding and Exploiting Most-Significant-Bit-Oracles in TLS-DH(E) - Merget, Robert; Brinkmann, Marcus; Aviram, Nimrod; Somorovsky, Juraj; Mittmann, Johannes; Schwenk, Jörg (30th USENIX Security Symposium (USENIX Security 21))

Experimental and Numerical Investigations into the Influence of the Process Parameters During the Deep Drawing of Fiber Metal Laminates - Heggemann, Thomas; Sapli, Hüseyin; Homberg, W. (Forming the Future)

Simplified Numerical Calculation of the Isothermal, Three-Dimensional, Non-Newtonian Flow Characteristics of Single-Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker

Non-Isothermal Calculation of the Pressure-Throughput-Characteristics of Single Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker

ITiCSE 2021: 26th ACM Conference on Innovation and Technology in Computer Science Education, Virtual Event, Germany, June 26 - July 1, 2021 - Working Group Reports

ITiCSE 2021: 26th ACM Conference on Innovation and Technology in Computer Science Education, Virtual Event, Germany, June 26 - July 1, 2021

Identity in K-12 Computer Education Research: A Systematic Literature Review - Große-Bölting, Gregor; Gerstenberger, Dietrich Karl-Heinz; Gildehaus, Lara; Mühling, Andreas; Schulte, Carsten (ICER 2021: ACM Conference on International Computing Education Research, Virtual Event, USA, August 16-19, 2021)

ITiCSE 2021 recap - Schulte, Carsten; A. Becker, Brett (ACM SIGCSE Bull.)

Joining of Sheet Metal and Thermoplastic Composites Using Injection Riveting - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes

Fügen von thermoplastischen Composites mit Metallteilen durch Spritznieten - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (Joining Plastics)

Influence of Plasmon Resonances and Symmetry Effects on Second Harmonic Generation in WS2–Plasmonic Hybrid Metasurfaces - Spreyer, Florian; Ruppert, Claudia; Georgi, Philip; Zentgraf, Thomas (ACS Nano)
The nonlinear process of second harmonic generation (SHG) in monolayer (1L) transition metal dichalcogenides (TMD), like WS2, strongly depends on the polarization state of the excitation light. By combination of plasmonic nanostructures with 1L-WS2 by transferring it onto a plasmonic nanoantenna array, a hybrid metasurface is realized impacting the polarization dependency of its SHG. Here, we investigate how plasmonic dipole resonances affect the process of SHG in plasmonic–TMD hybrid metasurfaces by nonlinear spectroscopy. We show that the polarization dependency is affected by the lattice structure of plasmonic nanoantenna arrays as well as by the relative orientation between the 1L-WS2 and the individual plasmonic nanoantennas. In addition, such hybrid metasurfaces show SHG in polarization states, where SHG is usually forbidden for either 1L-WS2 or plasmonic nanoantennas. By comparing the SHG in these channels with the SHG generated by the hybrid metasurface components, we detect an enhancement of the SHG signal by a factor of more than 40. Meanwhile, an attenuation of the SHG signal in usually allowed polarization states is observed. Our study provides valuable insight into hybrid systems where symmetries strongly affect the SHG and enable tailored SHG in 1L-WS2 for future applications.

Learning From Revisions: Quality Assessment of Claims in Argumentation at Scale - Skitalinskaya, Gabriella; Klaff, Jonas; Wachsmuth, Henning (Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics)